2008
DOI: 10.1002/ajmg.b.30698
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum conditons in myotonic dystrophy type 1: A study on 57 individuals with congenital and childhood forms

Abstract: Myotonic dystrophy type 1 (DM1) is an autosomal dominant disorder, caused by an expansion of a CTG triplet repeat in the DMPK gene. The aims of the present study were to classify a cohort of children with DM1, to describe their neuropsychiatric problems and cognitive level, to estimate the size of the CTG expansion, and to correlate the molecular findings with the neuropsychiatric problems. Fifty-seven children and adolescents (26 females; 31 males) with DM1 (CTG repeats > 40) were included in the study. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 70 publications
6
104
0
8
Order By: Relevance
“…Ekströ m et al) 19 . Assessment of gross motor function was made using the Hammersmith functional motor scale, 20 which is widely used to assess motor function in neuromuscular disorders, including DM1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ekströ m et al) 19 . Assessment of gross motor function was made using the Hammersmith functional motor scale, 20 which is widely used to assess motor function in neuromuscular disorders, including DM1.…”
Section: Methodsmentioning
confidence: 99%
“…10 DNA was extracted from peripheral blood lymphocytes and analysed for expansion of the CTG repeat in the DMPK gene. 19 …”
Section: Methodsmentioning
confidence: 99%
“…7,8 In addition to intellectual impairment, there is evidence of autism spectrum disorder and attention-deficit/hyperactivity disorder. 7,9 A prior cross-sectional survey study identified difficulty with communication and problems with hands and fingers as the issues that reduce quality of life in children. 10 While this work has helped to characterize the disease burden in children with CDM, it did not serially evaluate patients using clinical assessments.…”
mentioning
confidence: 99%
“…The earlier the onset of the disease, the more serious the symptoms (Harper 2001). Intellectual disability and neuropsychiatric disorders are common in congenital and childhood subforms of DM1 (Ekström et al 2008). …”
Section: Introductionmentioning
confidence: 99%